External Quality Assessment Data for Investigation of von Willebrand Disease: Focus on Relative Utility of Contemporary Functional von Willebrand Factor Assays. The United Kingdom National External Quality Assessment Scheme (UK NEQAS) Experience - Jennings, Ian; Reilly-Stitt, Chris; Lowe, Anna; Kitchen, Steve; Walker, Isobel (Seminars in Thrombosis and Hemostasis, 2022)
Von Willebrand disease (VWD) is one of the most common hereditary bleeding disorders. Effective management of patients and their families depends on accurate diagnosis and subtype classification, and quality assurance including participation in proficiency testing programs is essential to ensure the accuracy of the panel of assays required to achieve this diagnosis. We report here findings from recent external quality assessment (EQA) exercises, as well as from a questionnaire about diagnostic practices employed by centers in the United Kingdom National Quality Assessment Scheme (UK NEQAS) performing von Willebrand factor (VWF) assays. Plasma samples from donors with VWD, “normal” donors, the International Society for Thrombosis and Haemostasis Scientific Subcommittee (ISTH SSC) plasma standard, and whole blood samples were sent to participants in the UK NEQAS BC program for VWF investigation. Calibration of lot#5 of the ISTH SSC plasma standard was shown to give improved comparability between the recovered value from an EQA exercise and the assigned potency for VWF activity assays. Diagnostic accuracy and precision amongst UK NEQAS participants was good, with an average 99% of centers reporting the correct interpretation for normal, type 1 and type 2 VWD samples, 100% diagnostic accuracy for centers performing FVIII binding assays, and good agreement amongst centers performing multimeric analysis. Genetic analysis of the VWF gene by specialist centers demonstrated errors in the genotyping process in one center, but also demonstrated failings in the interpretation of results in other centers. Despite evidence of good laboratory accuracy and precision in their assays, a questionnaire identified marked variation in diagnostic criteria employed, underlining the importance of guidelines to support the diagnosis of VWD.
Keywords: von Willebrand factor; functional assays; external quality assessment